2011
DOI: 10.1007/s00213-011-2174-y
|View full text |Cite
|
Sign up to set email alerts
|

Prospective memory functioning among ecstasy/polydrug users: evidence from the Cambridge Prospective Memory Test (CAMPROMPT)

Abstract: Rationale: Prospective memory (PM) deficits in recreational drug users have been documented in recent years. However the assessment of PM has largely been restricted to self report measures that fail to capture the distinction between event based and time based PM.The aim of the present study is to address this limitation.Objectives: Extending our previous research we augmented the range laboratory measures of PM by employing the CAMPROMPT test battery to investigate the impact of illicit drug use on prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 43 publications
1
26
0
1
Order By: Relevance
“…Better performance on event-based compared to time-based PM has previously been observed on the CAMPROMPT in smokers, non-smokers (Heffernan et al 2010), ecstasy/polydrug users or cannabis users (Hadjiefhyvoulou et al 2011) and is consistent with the multi-process model of PM which proposes relatively greater involvement of either strategic or automatic processing in the retrieval of intentions depending on the resource demands of the task and salience of external cues (Einstein and McDaniel 1990;McDaniel and Einstein, 2000). Thus the greater saliency of the cue in eventbased tasks is proposed to trigger automatic or reflexive retrieval of the intention with active engagement of attention.…”
mentioning
confidence: 72%
“…Better performance on event-based compared to time-based PM has previously been observed on the CAMPROMPT in smokers, non-smokers (Heffernan et al 2010), ecstasy/polydrug users or cannabis users (Hadjiefhyvoulou et al 2011) and is consistent with the multi-process model of PM which proposes relatively greater involvement of either strategic or automatic processing in the retrieval of intentions depending on the resource demands of the task and salience of external cues (Einstein and McDaniel 1990;McDaniel and Einstein, 2000). Thus the greater saliency of the cue in eventbased tasks is proposed to trigger automatic or reflexive retrieval of the intention with active engagement of attention.…”
mentioning
confidence: 72%
“…Four cross-sectional studies with average abstinence periods ranging from 2 weeks to 20 years concluded that former marijuana users did not demonstrate memory problems compared to controls [5356]. A fifth cross-sectional study reported that impaired performance on verbal memory tasks persisted after 1 month of abstinence [57], but there were no checks to verify that that participants maintained abstinence.…”
Section: Resultsmentioning
confidence: 99%
“…Marijuana users also experience visual memory impairments [47, 49, 56, 5860]. Of the ten studies that reported verbal and visual memory results separately, six found verbal memory impairment in the context of intact visual memory abilities [5053, 57, 61], whereas none found impaired visual memory in the context of intact verbal memory.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decade, PM in SU(D) has been investigated in a number of cross-sectional studies, several of which show reduced event-and time-based PM performance in alcohol dependence, methamphetamine dependence, binge drinking, smoking, and cannabis and multiple illegal drug use (Griffiths et al 2012;Heffernan, O'Neill, and Moss 2012;Hadjiefthyvoulou et al 2011;Iudicello et al 2011;Bartholomew, Holroyd, and Heffernan 2010;Heffernan, O'Neill, and Moss 2010).…”
Section: Introductionmentioning
confidence: 99%